Association Between Periodontal Diseases and Preeclampsia - Atique, Fariha Arif, Anikah Kanwal, Tasneem Hafeez Alvi, Snober Faisal, Fawad Talat (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goal of this study is to examine whether or not periodontal disease is linked to preeclampsia. Methodology: One hundred participants (fifty cases and fifty controls) were recruited in the research after providing informed consent. Demographic details such as age, address, smoking, and parity was recorded. All periodontal disease pregnant women were allotted in cases group and normotensive pregnant women were allotted control group, the association between the two groups was investigated by applying O.R and chi square test. Results: Mean age was calculated as 25.81+3.91 years in cases and 24.71+5.73 years in control group, mean gestational age was 37.11+3.62 weeks in cases and 38.11+3.24 weeks in control group. The association of periodontal diseases and pre-eclampsia shows that 24(48%) in cases and 10(20%) in control group, O.R 3.69 and p-value=0.003. Conclusion: We came to the conclusion that there is a high link between the association between periodontal diseases and preeclampsia. Keyword: Pregnant women, periodontal disease, preeclampsia, association